Gender issues for first-level managers - Mortimore, Helen (Henry Stewart Talks, 2019)
Gender issues, Equality, Diversity, Culturally diverse teams, Intersectional identity, Banter, Motherhood penalty, Flexible working, Dress codes, Pay